2017
DOI: 10.1016/j.techsoc.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

What will it take to adopt smart glasses: A consumer choice based review?

Abstract: Wearable technologies have become a reality already. Their impact in some fields has already been seen. We explore the factors which are important and help the adoption of these technologies. Specifically we study the adoption factors of smart glasses. Technology adoption process depends on preferences and needs of people who use the systems under study. We explore these phenomenon through two frameworks: Product Characteristics and User Intention Characteristics. The purpose of the first framework is to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 42 publications
1
12
0
1
Order By: Relevance
“…Among the findings, the authors found that the ease of use of smart watches is indirectly related to the attitude towards the use of these wearable devices. e same results regarding wearable technologies were found by Chae [25] and Basoglu et al [26].…”
Section: Development Of Instruments To Measure the Acceptance Ofsupporting
confidence: 81%
“…Among the findings, the authors found that the ease of use of smart watches is indirectly related to the attitude towards the use of these wearable devices. e same results regarding wearable technologies were found by Chae [25] and Basoglu et al [26].…”
Section: Development Of Instruments To Measure the Acceptance Ofsupporting
confidence: 81%
“…The majority of studies have been performed in the pre-market period in an attempt to explain adoption within different settings. Hein and Rauschnabel (2016) itemized "experience in use of ARSGs in other settings, enjoyment, wearable comfort, social influence, and incentives" as factors of adoption at the individual level, while Basoglu et al (2017) suggested "enjoyment, self-efficacy, peer influence, risk, anxiety, health concern, and complexity." Adapa et al (2017) compiled a different list, which includes "battery heat, weight, form factor, interface, functionality, battery life, look and feel," while tom Dieck et al (2016) added "content requirement, content quality, personalized information, navigation, hedonism, and distraction" to other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Functionality has appeared to be an effective determining factor for the adoption of ARSGs (Rauschnabel et al, 2015;Basoglu et al, 2017), as these devices have the potential to create increased value in professional lives and personal use (Elder and Vakaloudis, 2015;Mitrasinovic et al, 2015).…”
Section: Research Framework and Hypothesesmentioning
confidence: 99%
“…From one side, the possibility to overlap digital and real context directly in front of the user's eyes, without an extra object like a smartphone, is a very interesting feature for non-verbal communication systems. On the other hand, however, those kinds of devices have not been vastly adopted yet, for reasons that space from technological issues to public hostility (Basoglu et al, 2017;Cipresso et al, 2018;Due, 2014). The first AR wearable interface that was diffused on a large scale, Google Glass, has been considered one of the biggest technological flops in history, and nowadays smart glasses are still far from being commonly accepted.…”
Section: Ar and Smart Glassesmentioning
confidence: 99%